China's rise in mainland ASEAN new dynamics and changing landscape - Suthiphand Chirathivat 1953-; Rutchatorn, Buddhagarn; Devendrakumar, Anupama; Wīra Sombūn (World Scientific Publishing Co. Pte. Ltd., 2019)
"The rationale for this volume on China's Rise in Mainland ASEAN: New Dynamics and Changing Landscapes stems from the rise in recent years of China, ASEAN's giant neighbor, and in its wake the significant economic, political, and socio-cultural developments in the ASEAN region. In the last two decades, China has successfully established itself as a powerful regional and global power, surpassing Japan in 2010 as the second largest economy of the world, and has become a major player in the affairs of South East Asian nations. At the same time, while China's spectacular growth makes it vulnerable in terms of expanding its global dependence, it also makes its neighbours equally vulnerable due to their growing dependence on China. All of these developments have led China through its evolving foreign policy to exert considerable influence on its immediate ASEAN neighbours in many complex ways. While the China-ASEAN bilateral relations are soaring, there are growing concerns among ASEAN member countries about the nature of China's engagement with ASEAN. In this context, this book focuses on China's influence on mainland ASEAN countries: Cambodia, Lao PDR, Myanmar, Thailand and Vietnam"--
Keywords: Association of Southeast Asian Nations; China; ASEAN.; China / Foreign relations / Southeast Asia; Southeast Asia / Foreign relations / China; China / Foreign economic relations / Southeast Asia; Southeast Asia / Foreign economic relations / China; Diplomatic relations; International economic relations; Southeast Asia; Aufsatzsammlung